THE SPEECH ACT ON MARK TWAIN’S THE PRINCE AND THE PAUPER - Cici Nur Indah Sari; Tuyami Tuyami (Universitas Stikubank (UNISBANK) Semarang, 2017)
This study has an objective to describe the form of locution and illocutionary speech act in Mark Twain’s novel, The Prince and the Pauper. Based on Austin’s theory, he distinguishes kinds of speech act, i.e., three ways of doing things with words; locutionary, illocutionary and perlocutionary. This study is qualitative and just analyzes locutionary and illocutionary. Qualitative research is a study using an assessment method or research method toward a problem. Source of this research applies for primary code and secondary code. The prime code is the novel The Prince and the Pauper, and the secondary code in this research applies for some articles and journal relate to this research about locution illocutionary speech act. Result of this research produces form of speech act in Mark Twain’s novel, The Prince and the Pauper.Index terms: Speech act, pragmatics, novel, locution, illocutionary